Development of Nanoparticle-Based Biodegradable Polymer Composite Film for Antifungal Drug Delivery in Prosthetic Joint Infection - Kale, Rupali; Deshkar, Sanjeevani Shekhar; Deshmane, Pooja Dattatray; Whagmare, Balasaheb (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Fluconazole is an antifungal agent of triazole class. Fluconazole is one of the most prescribed antifungal agents because of its excellent bioavailability, tolerability and side effect profile. To maintain drug concentrations within therapeutic levels in bone tissue for specific periods, antifungal agents must be re-administered when they are given systemically. Aim The aim of the present study was to develop a nanoparticle-based implantable drug delivery system of antifungal drug fluconazole for Prosthetic Joint Infection and it’s in vitro and in vivo evaluation. Materials and Methods Fluconazole loaded Chitosan Nanoparticles (CH-NP) were prepared by ionic gelation method and optimized for chitosan: TPP mass ratio, chitosan and fluconazole concentration. CH-NP were evaluated for particle size, polydispersity index, zeta potential, entrapment efficiency, FTIR, DSC, XRD and percent drug release. Nanoparticles were further incorporated in gelatine: chitosan composite film and formulations were optimized for chitosan: gelatin ratio, plasticizer concentration and cross-linker concentration. The developed composite film was tested for water absorption capacity, in vitro and in vivo biodegradation, toxicity and antifungal potency. Results and Discussion The optimized CH-NP demonstrated 458 nm particle size, 82.39% entrapment efficiency and 77.4% drug release after 4 hr. The chitosan-gelatine ratio of 1:10, glycerine concentration of 5% and formaldehyde concentration of 0.01% resulted in desired in vitro properties and sustained drug release up to 10 hr. The developed formulation showed potent antifungal efficacy and in vitro biodegradation within 3 days. The in vivo biodegradation studies of films in rats showed complete degradation of implant within 7 days of implantation. Histopathology studies revealed no acute toxicity of implanted formulation. Conclusion The developed Fluconazole loaded chitosan nanoparticle-based polymer composite film could be an effective formulation approach to prevent the fungal infections acquired during surgeries.
Keywords: Fluconazole; Nanoparticles; Chitosan; Implant; Prosthetic joint infection; Composite film